Characterisation of Shell Disease Syndrome in the Brown Crab, Cancer Pagurus, in a Discrete Irish Sea Fishery. Issue 1 (1st January 2014) - King, Nathan G.; Duncan, Peter F.; Kennington, Kevin; Wootton, Emma C.; Jenkins, Stuart R.
Abstract: Shell disease is the progressive degradation of a crustacean's exoskeleton through the secretion of chitinases and other enzymes from a suite of microorganisms. It affects a number of crustacean fisheries worldwide, through increased pre-capture mortality and rendering many individuals unsalable or with a reduced market value. The European edible crab (also known as the brown crab), Cancer pagurus Linnaeus, 1758, is highly susceptible to shell disease, but while intertidal populations have been comprehensively assessed, there has been little attention from a commercial fishery perspective. This study assessed the prevalence (% of catch infected) and severity (% cover of lesions on the carapace) of shell disease in the fishery around the Isle of Man for C. pagurus, in the Irish Sea. Shell disease was assessed in relation to sex and size, and the pattern of infection on ventral and dorsal surfaces described. A total of 2361 individuals was sampled between June and August 2012. Almost $25%$ of crabs were infected to some degree and of those infected an average of just over $2%$ of the carapace was covered by lesions. The proportion of individuals infected and the severity of infections was found to increase with size and was greater in males and those exhibiting limb losses. Differences in the pattern of lesions on the carapace between sexes suggest behavioural differences between genders can result in different patterns of individual infection. Both prevalence and severity of the disease varied considerably around the Isle of Man. Based on assessment of eight different fishing grounds, prevalence varied from as low as $15%$ of the population to as high as $35%$, while the severity of infection varied between $0.8%$ to almost $3%$ . These findings not only suggest that shell disease syndrome could be causing a significant economic loss in the fishery, but also that environmental factors may be driving the condition. However, further investigation is required to fully elucidate the environmental drivers of this syndrome.